5. ERECTOR SPINAE PLANE BLOCK FOR PERIOPERATIVE ANALGESIA IN RENAL TRANSPLANTATION WITH ULTRASOUND (Vietnam Journal of Community Medicine, 2023)
Objectives: Evaluation of the analgesia perioperative renal transplant of erector spinae plane (ESP)compared with PCA analgesia (patient-controlled analgesia) and adverse effects. Materials andMethods: A study on 60 patients with indications for kidney transplant surgery at the Center forSurgical Anesthesia - Viet Duc Hospital, randomly distributed into 2 groups of ESP and a controlgroup. Results: Age, height, weight, BMI, diagnosis, ASA, drug dosage and anesthetic method hadno difference between the two groups of ESP and PCA with p > 0.05. The time for the ESP group tofirst require analgesia in the group was 5.7 ± 2.45 hours, 1.76 ± 0.31 hours longer than the PCA groupalone. 24-hour morphine consumption of ESP 5.8 ± 3.5mg compared with PCA alone: 13.3± 6.5mgstatistically significant difference with p < 0.05. VAS scores at rest and movement of the group underanesthesia decreased statistically. Conclusion: ESP is an effective method of pain relief during andafter surgery, reducing the dose of morphine and reducing the amount of morphine consumption. Itis recommended to apply to enhance the effectiveness of postoperative pain relief.
Keywords: ESP, erector spinae plane block, analgesia, renal transplant.